The Effect Of Write-Pair-Share Technique Towards Students’ Writing Ability At SMAN 1 Unaaha - haslan haslan (Shautut Tarbiyah, 2017)
Abstract            The objective of this study was to find out if there is any significant effect on students’ writing ability using write-pair-share technique. The methodology of this study was quantitative. The design of this study was pre-experiment with one group pre-test and post test design. Sample of this study was students’ grade X-A of SMAN 1 UNAAHA. The result of the study show that there is significant effect on students’ writing ability using write-pair-share. It seemed by number of students who achieved the target score from good to average – excellent to very good or 14 above score level for vocabulary and 18 above score level for language use (grammar), which for vocabulary aspect from none increased to 25 students (83.33%), and for language use (grammar) aspect from none increased to 20 students (66.67%) who achieved target score. Conclusion of this study is using write-pair-share technique is effectively in learning process. Key Words: Write-Pair-Share Technique, Writing Ability